2021
DOI: 10.1063/5.0037409
|View full text |Cite
|
Sign up to set email alerts
|

Principal strain rate evolution within turbulent premixed flames for different combustion regimes

Abstract: The statistical behaviours of the principal strain rates and its evolution in turbulent premixed flames have been analysed using a three-dimensional Direct Numerical Simulations dataset of statistically planar turbulent premixed flames with different turbulence intensities spanning from the corrugated flamelets regime to the thin reaction zones regime. It has been found that the scalar gradient predominantly aligns collinearly with the most extensive principal strain rate within the flame for large Damköhler n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 78 publications
3
14
0
Order By: Relevance
“…This could be due to severe heat release across the flame brush (Dopazo et al 2015). In their recent work, Kasten et al (2021) reported a similar behavior using simple chemistry under forced turbulence in the reactants. A similar trend was previously reported in Dopazo et al (2015) for a flame under decaying turbulence in the corrugated flamelets regime with an Arrhenius one-step chemistry.…”
Section: Strain Rate and Curvature Dependence Of Thermal Flame Thicknessmentioning
confidence: 80%
See 4 more Smart Citations
“…This could be due to severe heat release across the flame brush (Dopazo et al 2015). In their recent work, Kasten et al (2021) reported a similar behavior using simple chemistry under forced turbulence in the reactants. A similar trend was previously reported in Dopazo et al (2015) for a flame under decaying turbulence in the corrugated flamelets regime with an Arrhenius one-step chemistry.…”
Section: Strain Rate and Curvature Dependence Of Thermal Flame Thicknessmentioning
confidence: 80%
“…A similar simplification has been previously performed in the literature, see e.g. Boger et al (1998); Chakraborty (2007); Han and Huh (2008); Dopazo et al (2015); Brearley et al (2020); Kasten et al (2021);Varma et al (2021).…”
Section: Flame Configurationmentioning
confidence: 83%
See 3 more Smart Citations